Factors affecting the development of skills in accounting professional necessary in the era of artificial intelligence (AI) in the Northeastern region - Dangmuenwai, Kasidit; Wuttikanaokkan, Linnapat (Journal of Management Science Nakhonratchasima University, 2025)
This research aimed to 1) analyze the level of factors related to the development of essential accounting skills in the AI ​​era in Northeastern Thailand, 2) assess the level of development of essential accounting skills in the AI ​​era in Northeastern Thailand, and 3) analyze the relationship between various factors and the development of essential accounting skills in the AI ​​era in Northeastern Thailand. The research population consisted of 382 accountants working in Northeastern Thailand, selected by using a purposive sampling method. Data were collected using a 5-point Likert-scale questionnaire. Descriptive statistics, including t-test, F-test, and multiple regression analysis, were used. The research results showed that the overall factors influencing the development of essential accounting skills in the AI era were high. The overall development of essential accounting skills in the AI era was also high. Furthermore, factors influencing the development of essential accounting skills in the AI ​​era, specifically technology, changes in the labor market, sustainability and ethics, and changes in standards and laws, had a statistically significant impact at the .05 level.